Mental Health of Pre-Service Training Teacher in Indonesia: Analysis between Psychological Well-Being and Emotional Regulation with Demographic Factors - Fatmawati, Hana; Purnomo, Reza Asep Adi; Rachman, Nabila; Nurwidawati, Desi; Santosa, Rizky Putra; Halida, Arfin Nurma; Henlianto, Michelle Octaviani (Universitas Negeri Surabaya, 2024)
Background: The mental health of pre-service teachers is essential as they manage the demands of early teaching and build professional skills. Many face challenges in psychological well-being and emotional regulation, impacting their classroom effectiveness and resilience. Objective: This study examines psychological well-being and emotional regulation among Indonesian pre-service teachers and the influence of demographic factors. Method: A quantitative correlational design was used, with data gathered from 583 pre-service teachers in Indonesian. Psychological well-being and emotional regulation were measured using validated scales, and ANOVA was employed to assess differences across demographic factors. Results: Results show that many pre-service teachers have low to medium levels of psychological well-being, with significant variation in emotional regulation abilities. Demographic factors—gender, age, employment status, and teaching placement—did not significantly affect these aspects. Conclusion: The findings indicate that PWB and ER are not significantly affected by demographic factors like age, gender, employment status, or teaching placement. This suggests that challenges in these areas are widely experienced across different demographic groups, emphasizing the universal.